Edukasi William Flexion untuk Mengatasi Low Back Pain pada Lansia di Wilayah Puskesmas Mojolaban Sukoharjo - Khairun Nisa; Farid Rahman; Eni Susilowati (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Mojolaban is one of the sub-districts in Sukoharjo Regency, Central Java, which has 15 villages. The district has Mojolaban main health center, Jatimalang auxiliary health center and Kustati Clinic. Low back pain (LBP) is a disease that is widely suffered in Sukoharjo Regency, according to the Sukoharjo Regency Health Office, LBP sufferers amounted to 3,670 people from 2018-2022. LBP is one of the health problems that is often not taken seriously by the community, especially the elderly. Even though if left unchecked it can interfere with daily life and reduce quality of life. The purpose of this counseling is to prevent, promote health related to LBP with the target participants of the Matahari Elderly Posyandu located in Ds. Wirun Mojolaban. The measurement used in this activity is a pre-test and post-test questionnaire to measure the understanding of the elderly. The results of the questionnaire showed a good improvement with an average pre test and post test increase of 50%. For this reason, posyandu cadres always follow-up so that the elderly can do this exercise not only during counseling but also at home.